APLIKASI PENGOLAHAN DATA DIIT MAKAN PASIEN PADA RUMAH SAKIT MAYANG MEDICAL CENTRE (MMC) JAMBI - simorangkir, lucy; Marbun, Mery Elisabeth (FORTECH (Journal of Information Technology), 2017)
Diet foods and beverages that are consumed on a regular basis every day, the amount and type of food needed in certain situations, such as the decrease or increase the weight. Diit done depends on age, weight, health condition of the number of activities carried out in a day. Destination Therapy Diit to obtain a good nutritional status, improve nutritional deficiency, resting the organs, adjust the intake / intake with the bodys ability, and weight change when necessary. At Mayang Hospital Medical Centre (MMC) Jambi pengecekkan patients do diet meal every day from the beginning of admission until discharge (recovered / died). Nutrition section shall ask the nurse the patients condition or a change in diet: eat patient at admission. The system used for this is still done by hand, thus slowing in the service of patients and wasting a lot of time to monitor changes and developments in the patients health. For it is necessary to build a Microsoft Visual Basic 6.0 application that aims to simplify the user to access any data that is needed, can reduce errors in feeding the patient as needed. The system will be built is designed so that users can shorten the time to process each data to be processed. With this application is expected to speed up data processing of patient food diet.